Shifting Priorities, Attitudes, and Institutional Change: Reflections on UNHCR at the Crossroads - Gorlick, Brian (Refuge: Canada's Journal on Refugees, 2001)
The international debate on refugee issues is in flux and has been influenced by a number of factors including post–cold war disinterest in refugees, the media, extraordinary humanitarian crises, and shifting attitudes among policy makers and the public. Over the last decade in particular, the Office of the United Nations High Commissioner for Refugees (UNHCR) has been given the task of providing protection and relief in large-scale humanitarian operations, some of which are unprecedented in size, level of conflict, and categories of persons provided assistance. In the new millennium and under new leadership, will UNHCR get back to “the basics of protection,” or will it continue to be asked to respond to humanitarian crises in the absence of other action by the international community? These are serious policy questions facing the Office.